Self-Love in Forgiveness and Boundaries in the Powder Room Talk: Discourse Analysis - Sundein, Izni (Language Horizon: Journal of Language Studies, 2023)
This research is entitled Discourse Analysis of Self-Love in Forgiveness and Boundaries in The Powder Room Talk which aims to identify the text structure in macrostructure, superstructure, and microstructure, and also to reveal the ideology. The method used is descriptive qualitative with the approach of Teun A. Van Dijk's theory. The data source was form of a textual transcript that was transcribed from the video. The researcher observed and verified the transcription to categorize the data into macrostructure, superstructure, and microstructure. Then, the data were analyzed in data reduction to find the important data and presented into discussion and find the ideology. The result; the macrostructure analysis reveals the talk show's main topic: discussing the true meaning of the word forgiveness and boundaries based on their life experiences. The superstructure analysis shows a schematic on the talk show which consist of opening, body, and closing in order to convey the discussion properly and regularly. The microstructure analysis: syntactic, semantic, stylistic, and rhetorical. The most common linguistic features found are the first singular pronoun (syntax), lexicon (stylistic), euphemism and repetition (rhetoric) as a strategy to emphasize statements, clarify information, attract attention. In addition to the text analysis, the researcher discovered the ideology of Cinta Laura in the talk show, that is about self-love in own-self.